Forecasting the potential area of an invasive species Cylindrocopturus adspersus LeConte (Coleoptera: Curculionidae) in Ukraine - Sergey Moroz; Andrew Fokin (Journal of Plant Protection Research, 2022)
The sunflower stem weevil, Cylindrocopturus adspersus LeConte is a quarantine intra-stem pest of sunflower, distributed mainly in the United States, and discovered in the Kherson region of Ukraine in 2020. The objective of this study was to establish a possible distribution zone of this species in Ukraine based on the results of bioclimatic modeling. The model was built by using programs DIVA GIS version 7.5.0 and BIOCLIM, which search for areas that are suitable for a particular organism, through geographic information systems and by comparing the world climate with the climate of areas in which it has already been identified. Analysis of the model shows that in Ukraine the pest can acclimatize in the Kherson region only (zone with up to 2.5% probability). Geographically, the territory is limited to 46−47° of north latitude and to 33−34° of north longitude. It is located on the Black Sea Lowland and covers territory lying no higher than 50 meters above the Black Sea level, whose land- -surface temperature in July averages more than 28°С. The North Crimean Canal and Krasnoznaamyansky Canal pass through the territory, which is limited in the south by Sivash, Karkinitsky Bay and Dzharilgatsky Bay of the Black Sea, in the west − by the Dnipro Delta, and in the north − by Kakhovka Reservoir and Kakhovskiy canal. The analysis of values of climatic predictors for the territories which are suitable for acclimatization of a phytophage demonstrated its high ecological plasticity and potential ability to move not only on coastal territories, but also on territories with a continental climate.